Harkaleh Watershed Ecological Capability Assessment for Agricultural Land with an Emphasis on the Sustainable Development - Varshosaz, Katayoon; Hassan, Elham Mubarak (European Journal of Sustainable Development, 2016)
According to this study, ecological capability evaluation of land to develop agricultural and range management land uses were done based on spatial multi criteria evaluation and ovelay methods in Harkale in Lali city, southwestern Iran,2014. Ecological capability evaluation of land is one of the basic problems in environmental science. Following determination of the basin boundary on watershed topographic map (1:25000) and, analog maps were digitized in GIS environment. Next, data analysis were valued based on data collection analytical hierarchy process (AHP) method that it is one of the most typical of MCDM methods. Using AHP method, hierarchy structure of criteria was given in three level including objective, main criteria and sub criteria and weight matrixes were completed based on expert’s opinion. Then, the matrixes were analyzed in Expert choice software to give of weight criteria. In next stage, weighting results of criteria were generalized to respective layers in GIS environment. Finally, 16data layers of ecological resources were overlaid and the final map of ecological capability of the study area was given and classified in six classes including very suitable, suitable, moderately suitable, less suitable, much less suitable and non developed parts. Also, using Makhdoum method, environmental units map was produced according to evaluation levels and overlaying of ecological data layers. Then, the final map of ecological capability of Harkale watershed for developing agriculture and range management land uses was given based on SQL method. The results showed that in AHP method, suitable development of agriculture and range management land uses are allocate 1005 and 1242 ha of the study area (3855 ha) while in Makhdoum method these area contained 713 and 1568 ha, respectively. Totally, Harkale watershed has moderate ecological capability for developing agriculture and range management land uses. Keywords: Ecological capability evaluation, Multi criteria evaluation, Analytical hierachy Process ( AHP) ,Makhdoom model,GIS